Deterioration of Respiratory Symptoms in Uncontrolled CPFE: A Case Report - Raffael, Frans; Tarigan, Amira Permatasari (Faculty of Medicine Universitas Airlangga, 2025)
Introduction: Chronic obstructive pulmonary disease (COPD) has a global impact on health and increases healthcare costs. Combined pulmonary fibrosis and emphysema (CPFE) combines interstitial lung disease (ILD) and emphysema. Excessive short-acting β2-agonist (SABA) usage escalates exacerbation risk, affecting prognosis. Case: A 44-year-old former smoker presented with worsening shortness of breath, cough, and weight loss. Examination showed respiratory distress, including wheezing. Initially, he was diagnosed with tuberculosis (TB) and COPD exacerbation. He regularly used jet nebulizers without medical supervision, and during the initial treatment, he developed acute respiratory failure, leading to acidosis. Treatment involved SABA and short-acting muscarinic-antagonist (SAMA), steroids, and oxygen therapy. In November 2023, his condition worsened, requiring emergency treatment. Radiological findings indicated CPFE. Management included nebulized medications, intravenous steroids, and antibiotics. Despite challenges, he rarely attended follow-up appointments after showing improvement, missing scheduled rehabilitation therapy, inhaler monitoring, comorbid therapy, and home oxygen monitoring. Conclusion: Combined pulmonary fibrosis and emphysema combines ILD and emphysema, causing severe respiratory impairment. Management mirrors that of COPD, involving inhalers, corticosteroids, and oxygen therapy.